Analisis Pengelolaan Perpustakaan Sebagai Sumber Belajar Siswa Sekolah Dasar - Rochayati, Sholikhah Dwi (Universitas Sarjanawiyata Tamansiswa, 2024)
The purpose of the study is to find out: the management of libraries as a source of student learning, to know library programs that can be used as learning resources for students, to find out the supporting and inhibiting factors for the use of school libraries. This research uses a qualitative approach. The research was conducted at SD Negeri Girisekar. Research data sources, principals, librarians, and teachers. Data collection techniques with interviews, observations and documentation. Data analysis techniques data collection, data reduction, data presentation and conclusion drawing. The validity of the data using techniques increases persistence and triangulation. The results showed that the implementation of library management has been carried out properly. Library programs include, sambe cabe program, sanak saku program, jam wajib kunjung program, pojok baca program. The principal strives to design a program of activities, actively follow the development of information, encourage the improvement of the quality of librarians, collaborate with, teachers, outsiders and parents, and innovative programs become supporting factors. The procurement of sarpras and materials is constrained by funds, the lack of discipline of librarians, the lack of knowledge of teachers in library management, and the lack of library personnel are the inhibiting factors.